Proteasome Activity Is Influenced by the HECT_2 Protein Ipa1 in Budding Yeast. Issue 1 (8th March 2018) - Lutz, Anne P; Schladebeck, Sarah; Renicke, Christian; Spadaccini, Roberta; Mösch, Hans-Ulrich; Taxis, Christof
Abstract: The ubiquitin–proteasome system (UPS) controls cellular functions by maintenance of a functional proteome and degradation of key regulatory proteins. Central to the UPS is the proteasome that adjusts the abundance of numerous proteins, thereby safeguarding their activity or initiating regulatory events. Here, we demonstrate that the essential Saccharomyces cerevisiae protein Yjr141w /Ipa1 (Important for cleavage and PolyAdenylation) belongs to the HECT_2 (homologous to E6-AP carboxyl terminus_2) family. We found that five cysteine residues within the HECT_2 family signature and the C-terminus are essential for Ipa1 activity. Furthermore, Ipa1 interacts with several ubiquitin-conjugating enzymes in vivo and localizes to the cytosol and nucleus. Importantly, Ipa1 has an impact on proteasome activity, which is indicated by the activation of the Rpn4 regulon as well as by decreased turnover of destabilized proteasome substrates in an IPA1 mutant. These changes in proteasome activity might be connected to reduced maturation or modification of proteasomal core particle proteins. Our results highlight the influence of Ipa1 on the UPS. The conservation within the HECT_2 family and the connection of the human HECT_2 family member to an age-related degeneration disease might suggest that HECT_2 family members share a conserved function linked to proteasome activity.